Vagão Sustentável: Extension Practices for the SDGs - Insights from a UFVJM Experience in the Mucuri Valley (International Journal of Geoscience, Engineering and Technology, 2025)
This paper presents the results carried out at the Mucuri Campus of the Federal University of the Jequitinhonha and Mucuri Valleys (UFVJM), in Teófilo Otoni, Minas Gerais, held in reference to World Environment Day. The initiative aimed to raise awareness among the academic and local community regarding responsible consumption, environmental education, and solidarity. The actions included a swap fair, ecological thrift store, donation drive, selective waste collection, and seedling distribution, all conducted in an integrated and coordinated manner. Participants included students, faculty members, administrative staff, representatives from ASCANOVI, the State Institute of Forests (IEF), and elderly residents from the Vila Esperança neighborhood in the city. As outcomes, food and clothing were collected and donated to the “Pão Nosso de Cada Noite” Project, approximately 50 native and fruit tree seedlings were distributed by the IEF, and recyclable waste was properly disposed of, reinforcing the sustainable dimension of the activity. The experience was aligned with five Sustainable Development Goals (SDGs) from the UN’s 2030 Agenda: SDG 1 - No Poverty, SDG 11 - Sustainable Cities and Communities, SDG 12 - Responsible Consumption and Production, SDG 13 - Climate Action, and SDG 15 - Life on Land, demonstrating the potential of university extension as a tool for socio-environmental transformation and the strengthening of territorial sustainability.
Keywords: Exchange fair; Environmental sustainability; Responsible consumption; UN 2030 Agenda